SYSTEM FOR PREDICTING DISCHEARGES OVER THE HIGH WATER PERIOD THROUGH THECLASSIFICATION TECHNIQUES DATA: CASE OF THE GAMBIA RIVER BASIN OF MAKO - Faye, C (university of eloued -جامعة الوادي, 2019)
This article examines the trend of flow during the high water period(from July till November) in the basin of Gambiameasured at the Mako station of over 2004-2013 period. Methodology consisted at first in calculation and in standardizationof data by the method of z-score of some statistical parameters (average, maximum, minimum, range and standard deviation). Obtained series were afterward submitted to classifications techniques such as k-means clustering and Agglomerative Hierarchical Clustering (AHC) of Time Series Data Mining to cluster and discover the discharge patterns in terms of the autoregressive model.. From these methods, a forecast modelhas been developed for the discharge process on average over these years. This study presents basin flow dynamics in high water periodfrom Time Series Data Mining technique
article
Keywords: data Mining, flow, forecast model, hydrological process, clustering; technics